Domiciliary consultations: some facts and questions. Issue 6644 (30th July 1988) - Fry, J.; Sandler, G.
Abstract : The domiciliary consultation scheme introduced at the start of the NHS enables joint consultation between a consultant and general practitioner in a patient's home when the patient cannot attend hospital on medical grounds. Consultants claim a fee from the NHS, general practitioners do not. Data from the Department of Health and Social Security on domiciliary consultations in England and Wales during 1981-6 were analysed. The number of domiciliary consultations fell during 1981-6 from 429, 759 in 1981 to 387, 394 in 1986, a fall of 10%, whereas the numbers of consultants and general practitioners increased by 1404 (12%) and 2400 (10%), respectively. The yearly rate of domiciliary consultation per consultant fell by 19% from 36 in 1981 to 29 in 1986 and that per general practitioner by 18% from 18 to 15. In 1986 geriatric medicine had the highest rate of domiciliary consultation per consultant (187) followed by psychiatry (89), general medicine (52), dermatology (49), rheumatology (42), general surgery (36), gastroenterology (35), thoracic medicine (34), and orthopaedics (30). In 1986 all specialties apart from clinical pharmacology and therapeutics and clinical genetics showed a decrease in the yearly rate of domiciliary consultation when compared with the rate for 1981. Domiciliary consultation seems to have become a domiciliary visit by the consultant alone. At an estimated cost of about 20m pounds for 1988 the scheme needs critical evaluation.